(3GdcGaj aj GdMOjKs - (3Gdcdjfj, CHh LYaQ, Gdcdjfj, eMeO Hf jYbhH Hf ESMGb, J (B329(3g` (B941(3es
(3ChdgG (B:s
(3ChdgG(B: (3YdjgeG GdSdGe aj bhd Gddg YR hLd hGPcQ Hc EPG fSjJ, bGd EPG Mda GdQLd afSj Cf jSJKfj adjSJKf EPG PcQs
(3BNQgG (B:s
(3BNQgG(B: (3CMeO Hf eMeO Yf eMeO Hf jMji Yf ZjGK Hf EHQGgje Yf CHj YHO Gddg Ydjg GdSdGe(B: (3Ef CejQ GdeDefjf cGf dG jPHM GdTGI YfO GdTGI hdG GdLRhQ YfO GdLRhQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 145s
(3GdPQjYI, L (B17: 160s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs